ADVENTISM AND MILITARY SERVICES: AMERICAN CIVIL WAR, WORLD WAR I, AND WORLD WAR II - Kelendonu, Michael Andrew (Klabat Theological Review; Vol 3 No 2 (2022): Klabat Theological Review, 2022)
The Adventist Church's history demonstrates that it may survive significant conflicts by using noncombatant service. As a Member of the Seventh-day Adventist Church, sometimes have to meet the challenge of conscription as the country is going through a crisis. Violence is not by God's word and is contrary to the concept of God's love. But on the other hand, church members must be good citizens. Therefore, the principle that must be upheld by every member of the church is to remain loyal to the country's constitution as long as it does not violate God's law. However, the church is not recommended that members volunteer for military service. Yet, Adventists can provide support through prayer, medical assistance, and food, provide space for the homeless, and actively spread the call for peace. Keywords: God’s law, military service, noncombatant service, principle